Study on nematodes (Pratylenchus spp.) on Arabica coffee in the Northwestern Vietnam - Thiep, N. V.; Soytong, K.; Oanh, N. T. K.; Hung, P. M. (International Journal of Agricultural Technology, 2019)
Arabica coffee is one of the most important crop grown in Northwestern Vietnam. The growing area is estimated to be 20,000 ha, accounting for approximately 40% of Vietnam’s Arabica coffee area, and it mainly distributed in Son La and Dien Bien provinces. The climate and elevation of those areas are suitable for growing Arabica coffee. Especially, the coffee is recognized as one of the high quality in the world trade. However, Arabica coffee cultivation in this region has threatened by nematode disease, causing leaf fall, twig dieback, dry fruit and leading to reduce productivity. The survey results of 19 tea coffee gardens in 2 provinces in 2018 had 84.81% of the gardens infected with Pratylenchus spp. The nematode density ranged from 21.91 to 48.3 individuals/ 100g of soil and from 43.5 to 99.2 individuals/ 2g roots. After 6 months, infection of Pratylenchus spp in plants with the density of 10, 100 and 500 individuals/pot, in greenhouse conditions, disease index was 31.45%, 62.48% and 84.78%, respectively. It is the first report to detect Pratylenchus spp ijn Arabica coffee in Muong Ang (Dien Bien) and Son La.